Energy efficient campus landscaping for mitigation of climate change effects - AHMADZADEH, REZA; DAS, D K; SINDHU, S S; SAHOO, R N; PRASAD, K V (The Indian Journal of Agricultural Sciences, 2016)
An experiment was conducted within the Indian Agricultural Research Institute (IARI) campus with 5 selected arboriculture tree species, namely, Ficus religiosa, Ficus infectoria, Azadirachta indica, Alestonia scholaris and Morus alba to compare their modifying capacity of thermal environment below the canopy with open space during peak summer months (May- June) and winter months (December-January) of 2010-11. Tree species and open space were treated as treatments (6) and 4 replications were taken for each treatment. During summer afternoon of 2010, the open space recorded an average temperature of 41.0ÂºC. Temperature below the canopy was reduced by each species. Maximum reduction (7.31%) was observed below the canopy of Ficus infectoria (38.0 oC), followed by Morus alba (38.4 oC), minimum reduction to 38.7 oC was observed below the canopy of Alestonia scholaris. During winter afternoon of 2010-11, the open space recorded an average temperature of 24.0oC. Maximum reduction to 19.5 oC was observed below the canopy of Ficus infectoria, followed by Ficus religiosa (19.6 oC), Azadirachta indica (19.7 oC), Alestonia scholaris (20.1 oC) and Morus alba (20.8 oC). An average temperature of 7.7oC was observed in the winter morning throughout the season in the open space and an increase in below canopy temperature was observed under each tree species. However, Morus alba recorded the highest increase to 8.5oC, followed by Ficus religiosa, Azadirachta indica, Alestonia scholaris (8.3oC each). The lowest increase was observed under Ficus infectoria (7.9oC). The maximum increase in the morning temperature and minimum reduction in that at afternoon was desired in the winter at Delhi for comfort.